Analisis Strategi Pemasaran Dalam Meningkatkan Volume Penjualan Pada Koperasi Pegawai Republik Indonesia (KPRI) “Bung” LLDIKTI Wilayah IX - Rismoyo Hk Hasanuddin; Renny Mointi; Khairinah Rosyadah (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The purpose of this study was to determine the extent to which marketing strategy analysis affects sales volume. Koperasi Pegawai Republik Indonesia (KPRI) which is engaged in retail sales and savings and loans is the subject of this research. In this study, a sample of ten people was selected, and the data were analyzed using basic linear regression analysis. Data were collected using a questionnaire. The data analysis method uses hypothesis testing and basic linear regression analysis tools. Based on the research results, the marketing strategy variable (X) simultaneously has a positive and negligible effect on sales volume (Y), which means that if the marketing strategy is not effective, the sales volume will not increase.